Design of Nanoparticle Systems by Controllable Assembly and Temporal/Spatial Regulation. (30th August 2019) - Fang, Ruochen; Liu, Mingjie; Jiang, Lei
Abstract: Nanoparticles (NPs) have been studied for several decades, and outstanding advancements have been made involving fabrication methods and various properties for many different applications. NP assemblies exhibit collective properties that are superior to the properties of individual NPs, and their assembly behavior is significantly affected by interparticle interactions and surrounding layers. The temporal/spatial regulation of NPs and the active species present in NP systems are crucial for achieving desirable performances. Here, the interparticle interactions, surrounding materials (especially ligands), and temporal and spatial regulation are the main topics discussed. The principles and classical examples of these regulation strategies are provided, and the resulting NPs regulated by these strategies exhibit remarkable properties and have great potential for various applications. Finally, the future prospects of the NPs are outlined with respect to the surface modification, temporal and spatial regulation, as well as the binary cooperative complementary principle. Abstract : Various nanoparticles can be regulated by four different strategies including control of interparticle interactions (noncovalent bonds, magnetic, electrostatic, van der Waals forces, etc.), ligand engineering (ligand exchange and ligand collapse), temporal regulation (such as lifetime of active species), and spatial regulation (such as distribution of active species). The final products have potential applications in multiplexing, analyte‐detection, photocatalysis, etc.